HUBUNGAN ASPEK KLINIS DAN LABORATORIUM DENGAN TIPE SINDROM NEFROTIK PADA ANAK - Mamesah, Robin Samuel; Umboh, Adrian; Gunawan, Stevanus (e-CliniC, 2016)
Abstract: Nephrotic Syndrome (NS) is one of the most frequent glomerular diseases in children marked with proteinuria, hypoalbuminaemia, and edema with or without hypercholesterolemia. Approximately there are six cases of NS per year every 100.000 child aged less than 14 years old in Indonesia with ratio between males and females 2:1. Based on therapy, NS is categorized into Steroid Sensitive Nephrotic Syndrome (SSNS) and Steroid Resistant Nephrotic Syndrome (SRNS). This study aimed to obtain the relationship between clinical and laboratory aspects with NS type in children. This was a retrospective analytical study conducted by using SSNS and SRNS patient data of the medical record in Department of Pediatric Prof. Dr. R. D. Kandou Hospital Manado. Daya were categorized into identity, age, blood pressure, proteinuria, hematuria, as well as albumin and cholesterol levels. The results showed that there were 29 SN patients (18 patients of SSNS and 11 patients of SRNS) consisted of 17 males (59%) and 12 females (41%). The statistical analysis showed that there was no significant correlation among sex (p=0.064), age (p=0.064), edema (p=0.138), systolic pressure (0.283), diastolic pressure (p=0.701), proteinuria (p=0.999), hematuria (p=0.060), albumin (p=0.175), and cholesterol (p=0.814) in both of SSNS and SRNS patients. Conclusion: There was no relationship between sex, age, blood pressure, proteinuria, hematuria, albumin, and cholesterol related to SSNS and SRNS. Keywords: nephrotic syndrome, proteinuria, SSNS, SRNSÂ Abstrak: Sindrom nefrotik (SN) adalah salah satu penyakit glomerulus yang sering ditemukan pada anak, yang ditandai dengan proteinuria, hipoalbuminemia, dan edema dengan atau tanpa hiperkolesterolemia. Diperkirakan enam kasus per tahun tiap 100.000 anak kurang dari 14 tahun di Indonesia dengan perbandingan antara laki-laki dan perempuan 2:1. Sindrom nefrotik berdasarkan respon terapinya terbagi menjadi sindrom nefrotik sensitif steroid (SNSS) dan sindrom nefrotik resisten steroid (SNRS). Penelitian ini bertujuan untuk mengetahui hubungan aspek klinis dan laboratorium dengan tipe SN pada anak. Jenis penelitian ini analitik retrospektif pada pasien SNSS dan SNRS berdasarkan data rekam medik di Bagian Ilmu Kesehatan Anak RSUP Prof. Dr. R. D. Kandou Manado. Data dikumpulkan meliputi identitas, usia, tekanan darah, proteinuria, edema, hematuria, hematuria, serta kadar albumin dan kolesterol. Hasil penelitian memperlihatkan 29 pasien SN terdiri dari 18 pasien SNSS dan 11 pasien SNRS. Laki-laki sebanyak 17 kasus (59%) dan perempuan 12 kasus (41%). Tidak didapatkan hubungan pada jenis kelamin (p=0,064), usia (p=0,064), edema (p=0,138), tekanan darah sistolik (p=0,283), tekanan darah diastolik (p=0,701), proteinuria (p=0,999), hematuria (p=0,060), albumin (p=0,175), kolesterol (p=0,814) pada kedua kelompok. Simpulan: Tidak terdapat hubungan antara jenis kelamin, usia, tekanan darah, proteinuria, hematuria albumin dan kolesterol dengan SNSS dan SNRS.Kata kunci: sindrom nefrotik, proteinuria, SNSS, SNRS.